Gossip and social exclusion in females: Do they have positive or negative consequences for social behaviour? - Cristina, Stephanie J. (University of Ottawa (Canada), 2000)
In the past, studies of aggression focussed almost exclusively on physical aggression; findings revealed that males were more aggressive than females. Recently, interest in female aggression has been rekindled due to the suggestion by Crick and others that females aggress primarily by attacking personal relationships, (i.e., gossiping about others, excluding them from play groups, manipulating friendships); this form of aggression has been termed "relational aggression". Numerous studies have examined the relationship of relational aggression to negative outcomes such as peer rejection, loneliness and depression. However, relational aggression may fulfil a normative function in female social development by serving to create and maintain the intimate dyads that are the hallmark of girls' social interactions. In the present research, the relationship of gossip and exclusion to friendship intimacy and social competence was examined. Eighty-seven girls, 39 drawn from grades 4--5 and 48 drawn from grade 8 participated in the study. Engaging in negative gossip and exclusion were predictive of lower peer acceptance, which partially supported the hypothesis that these are dysfunctional behaviours. However, support for the positive role of these behaviours was obtained within the realm of friendship. Exclusion of peers from play was predictive of friendship intimacy in younger subjects, and interview data further supported the idea that these behaviours may help create and maintain intimate dyadic friendships: girls reported that gossip is most likely to occur in the presence of a best friend, and that the motivation behind exclusion is often preservation of a best friendship. Positive gossip, included with negative gossip in previous research, emerged as an important predictor of peer acceptance and friendship intimacy.
Keywords: Psychology, Social.